The Role of the Village Head in the Development of Badan Usaha Milik Kampung (BUMKam) in Maredan Barat Village - Dafetta Fitri Linda; Siti Ativa Putridiani (Universitas Negeri Padang, 2026)
This study aims to explore the role of village heads in the development of Village-Owned Enterprises (BUMKam) in Maredan Barat Village, Tualang District, Siak Regency. Village heads play a crucial role in implementing village governance processes for the welfare and progress of the community. This study is a descriptive qualitative study; the methodology used is based on observation, interviews, and documentation. Data analysis involves three key aspects: data reduction, data presentation, and elaboration of conclusions. This study found three characteristics: (1) as an inspirator, who inspires BUMKam managers to improve performance and use BUMKam services according to their needs; (2) as a facilitator, who helps BUMKam managers access education and training in BUMKam management, and facilitates the business start-up process for the community; and (3) as a driver, who motivates the community to use BUMKam services.